Pengaruh Corporate Social Responsibility Terhadap Accrual Quality Pada Perusahaan Sektor Aneka Industri Di Indonesia - Ferry Aditya; Juniarti Juniarti (Business Accounting Review, 2016)
The affect of corporate social responsibility (CSR) on financial performance had been studied before. However, there were only a few studies about the effect of CSR on earning quality and each research had different finding. The aim of this research was to examine the affect of CSR toward earning quality which measured by accrual quality in miscellaneous industry firm listed in Indonesia Stock Exchange (IDX).CSR was measured by using GRI Index 3.1, whereas earning quality was measured by using accrual quality. There were two control variables used in this research: firm size and leverage. This study was conducted on miscellaneous industry firms in Indonesia in the period of 2009 to 2013 with a total sample of 92 firm years.The results of this research indicated that corporate social responsibility and leverage had no influence on accrual quality. However, firm size had positive influence toward accrual quality.